Eff ect of the aqueous leaf extract of Anchomanes diff ormis on the glucose level and organ/body weight ratio of Wistar rats - MacDonald Idu, Ovuakporie-Uvo Oghale (Journal of Medicinal Herbs and Ethnomedicine, 2015)
Anchomanes difformis (Araceae) is a plant with many reported therapeutic properties. This study is aimed at testing the blood sugar level and organ-to-body weight ratio effect of the aqueous leaf extracts of A. difformis, as measures of toxicity of the plant in a short term. Blood sugar test was done using a handy glucometer while organ-to-body weight ratio analysis was carried out following standard methods. Results got show that A. difformis had no effect on the blood glucose level and organ-to-body weight ratio on rats. A robust toxicity analysis of A. difformis aqueous leaf extract to further find out more proofs that the plant is safe for human subjects is recommended.